Incentivizing Responses in International Organization Elite Surveys: Evidence from the World Bank - Heinzel, Mirko; Weaver, Catherine; Briggs, Ryan (Journal of experimental political science, 2025)
Scholars of International Organizations (IOs) increasingly use elite surveys to study the preferences and decisions of policymakers. When designing these surveys, one central concern is low statistical power, because respondents are typically recruited from a small and inaccessible population. However, much of what we know about how to incentivize elites to participate in surveys is based on anecdotal reflections, rather than systematic evidence on which incentives work best. In this article, we study the efficacy of three incentives in a preregistered experiment with World Bank staff. These incentives were the chance to win an Amazon voucher, a donation made to a relevant charity, and a promise to provide a detailed report on the findings. We find that no incentive outperformed the control group, and the monetary incentive decreased the number of respondents on average by one-third compared to the control group (from around 8% to around 5%).